Analisis Numerik Sambungan Bolted Extended End Plate (BEEP) Menggunakan Program Bantu ANSYS - Dinda Almirah Hariadi (Pusat Publikasi Ilmiah LPPM Institut Teknologi Sepuluh Nopember, 2025)
The 1994 Northridge earthquake caused significant damage to steel structure buildings, particularly at connections, with cracks frequently appearing in welded areas and, in severe cases, propagating to flanges and column webs. This study evaluates the behavior of Bolted Extended End-Plate (BEEP) connections under cyclic loading, comparing them to the experimental results of Shi et al. using ANSYS software. The evaluation focuses on moment capacity, rotational capacity, and failure modes. The result from Shi et al. showed moment and rotation capacities of 320.10 kN-m and 3.5%, respectively. Numerical results showed the moment and rotation capacity of 327.86 kN-m and 4.3%, with a margin of error of 2.37%. The failure modes in the numerical model are almost similar to the experimental results. Therefore, the assumption is that the parameters used are close to the values applied in the experimental testing. As a result, the numerical model has been validated by the experimental result.